Capacitación gerencial y responsabilidad social del director educativo en escuelas del municipio Simón Bolívar / Managemental qualification and social responsibility of the educative director in schools of the municipality Simón Bolívar - Ortega, Gisela; Fossi, Leonardo; Castro, Luis (Impacto Científico, 2020)
Resumen La investigación tuvo como objetivo general describir la capacitación gerencial y la responsabilidad social ejercida por el director educativo en las escuelas del Municipio Simón Bolívar. Las bases teóricas están relacionadas con los siguientes autores: Capacitación gerencial de Koontz y weihrich (2003, Rue y Byars (2002), Reza (2004), Milkovich y Boudreau (2003); Responsabilidad Social de Lander (2006), Bowen (2002), Gertsacov (2003), Epstein (2004), Cannon (2004) y Esguerra (2002). Se utilizó un tipo de investigación descriptiva, con diseño de campo, no experimental, transversal, correlacional. La población estuvo conformada por 13 directivos de las 19 escuelas del Municipio Simón Bolívar del Estado Zulia. La estadística descriptiva aplicada a los datos recolectados permitieron llegar a la conclusión de que existe un nivel de correlación significativa, altamente positivo, entre la capacitación gerencial y la responsabilidad social ejercida por el director educativo; concluyendo que el mejoramiento de la primera variable, repercutirá ampliamente en la aplicación y efectividad de la segunda; mediante el favorecimiento del análisis y comprensión de los contenidos abordados, según la necesidad de la escuela, la comunidad y los grupos de dirección. Abstract The research was aimed at describing overall management training and social responsibility exercised by the director of education in the schools of the municipality Simon Bolivar. The theoretical bases are related to the following authors: Management training Koontz and Weihrich (2003 Rue and Byers (2002), Reza (2004), Milkovich and Boudreau (2003), Social Responsibility Lander (2006), Bowen (2002) , Gertsacov (2003), Epstein (2004), Cannon (2004) and Esguerra (2002). a kind of descriptive research was used with field design, non experimental, transversal, correlation. The population consisted of 13 directors of the 19 schools of the municipality Simon Bolivar in Zulia State Descriptive statistics applied to the collected data allowed to conclude that there is a significant level of correlation, highly positive, including management training and social responsibility exercised by the school principal. Concluding the improvement of the first variable, widely impact on the implementation and effectiveness of the second, by favoring the analysis and understanding of the content addressed as needed school, community and leadership groups.